DEVELOPMENT OF A LAN SIMULATION TOOL BASED ON WINDOWS ENVIRONMENT (Journal of Engineering, 2009)
The Internet’s rapid growth has spurred the development of new protocols and algorithms to meet changing operational requirements such as security, multicast transport, mobile networking, policy management, and quality of service support. Development and evaluation of these operational tools requires answering many design questions. This work proposes a computer network simulation program, devoted for wired LAN systems. The simulator would be able to work under Microsoft Windows NT platforms, also it has the potential to provide an emulation environment which should be suitable for testing protocols above the TCP layer under the Windows NT platform supported network layers, and offering scalability by running the simulator under distributed network system.